A systematic review and meta‐analysis on basic psychological need satisfaction, motivation, and well‐being in later life: Contributions of self‐determination theory. Issue 1 (9th June 2019) - Tang, Minmin; Wang, Dahua; Guerrien, Alain
Abstract: As the population ages, it is important to understand the factors that contribute to well‐being in the elderly. The purpose of this study is to perform a systematic review and meta‐analysis of research on well‐being among elderly people conducted particularly within the framework of self‐determination theory and, more precisely, to study the relationships among basic psychological need satisfaction, motivation, and well‐being. Therefore, a systematic search of the literature was conducted using the databases PsycINFO, PsycARTICLES, Academic Onefile, MEDLINE, Science Direct, and ERIC to find studies published in English and French. China National Knowledge Infrastructure (CNKI) was used to find studies published in Chinese. Ultimately, 23 studies (mainly from the United States, Canada, and Europe; no studies published in China were found) in the field of aging were used for the systematic analysis, 17 of which were used for the meta‐analysis. The results reported in these publications are relatively congruent with the idea that basic psychological need satisfaction and motivation (autonomous types) are positively associated with positive indicators of well‐being (meaning in life, life satisfaction, positive affect, self‐esteem, etc.) and negatively associated with negative indicators of well‐being (depression, apathy, etc.).